Are hospitalized or ambulatory patients with heart failure treated in accordance with European Society of Cardiology guidelines? Evidence from 12 440 patients of the ESC Heart Failure Long‐Term Registry. (October 2013) - Maggioni, Aldo P.; Anker, Stefan D.; Dahlström, Ulf; Filippatos, Gerasimos; Ponikowski, Piotr; Zannad, Faiez; Amir, Offer; Chioncel, Ovidiu; Leiro, Marisa Crespo; Drozdz, Jaroslaw; Erglis, Andrejs; Fazlibegovic, Emir; et al.
<x xml:space="preserve">Abstract</x> Aims To evaluate how recommendations of European guidelines regarding pharmacological and non‐pharmacological treatments for heart failure (HF) are adopted in clinical practice. Methods and results The ESC‐HF Long‐Term Registry is a prospective, observational study conducted in 211 Cardiology Centres of 21 European and Mediterranean countries, members of the European Society of Cardiology (ESC). From May 2011 to April 2013, a total of 12 440 patients were enrolled, 40.5% with acute HF and 59.5% with chronic HF. Intravenous treatments for acute HF were heterogeneously administered, irrespective of guideline recommendations. In chronic HF, with reduced EF, renin–angiotensin system (RAS) blockers, beta‐blockers, and mineralocorticoid antagonists (MRAs) were used in 92.2, 92.7, and 67.0% of patients, respectively. When reasons for non‐adherence were considered, the real rate of undertreatment accounted for 3.2, 2.3, and 5.4% of the cases, respectively. About 30% of patients received the target dosage of these drugs, but a documented reason for not achieving the target dosage was reported in almost two‐thirds of them. The more relevant reasons for non‐implantation of a device, when clinically indicated, were related to doctor uncertainties on the indication, patient refusal, or logistical/cost issues. Conclusion This pan‐European registry shows that, while in patients with acute HF, a large heterogeneity of treatments exists, drug treatment of chronic HF can be considered largely adherent to recommendations of current guidelines, when the reasons for non‐adherence are taken into account. Observations regarding the real possibility to adhere fully to current guidelines in daily clinical practice should be seriously considered when clinical practice guidelines have to be written.